The Impact of Service Quality, Facilities, and Room Cleanliness Toward Customer Satisfaction in Banyan Tree Resort Bintan - Andrea Michael Oei; Angel Violeta Prationo; Christopher Lionggodinata; Felix Pangsawira; Natasya Valentine; Viona Rosalina (MultiTech Publisher, 2021)
This study examines the critical determinants of customer satisfaction in the context of Banyan Tree Resort Bintan, a luxury resort destination. Drawing on a mixed-method approach combining quantitative surveys and qualitative interviews with guests, our research sheds light on the pivotal role of service quality, facilities, and room cleanliness in shaping overall guest satisfaction. Preliminary findings underscore that superior service quality, encompassing attributes such as responsiveness, reliability, assurance, empathy, and tangible aspects, significantly influences guest satisfaction levels. Furthermore, the quality and diversity of resort facilities, coupled with the cleanliness of guest rooms, emerged as key factors closely linked to guest contentment. These insights provide valuable guidance for resort management in their pursuit of enhancing guest experiences and fostering customer loyalty, ultimately reinforcing the resort's position in the competitive hospitality industry